Maternal Mortality in the United States: Recent Trends, Current Status, and Future Considerations. Issue 3 (September 2021) - Joseph, K.S.; Boutin, A.; Lisonkova, S.; Muraca, G.M.; Razaz, N.; John, S.; Mehrabadi, A.; Sabr, Y.; Ananth, C.V.; Schisterman, E.
Abstract : ( Obstet Gynecol . 2021;137:763–771) Despite what reputable publications have lead health physicians and experts to believe, reports from the National Center for Health Statistics show United States maternal mortality rates have not increased, rather the surveillance of maternal deaths has improved.